A low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios, its manufacturing method and application

By optimizing the cable structure and materials, adopting silver-plated copper wire conductors, multi-layer insulation and shielding design, and combining dynamic cross-linking and interlocking fixation, the loss and stability problems of traditional cables in high-frequency vibration scenarios are solved, achieving low-loss and highly stable signal transmission.

CN120767031BActive Publication Date: 2025-12-02CHENGDU DATANG CABLE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511285498.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-10
Publication Date
2025-12-02
Estimated Expiration
2045-09-10

AI Technical Summary

Technical Problem

Traditional twisted-pair digital communication cables are prone to problems such as interlayer delamination, microsphere displacement, unstable characteristic impedance, and high return loss under high-frequency vibration scenarios, which cannot meet the requirements of 40Gbps high-speed transmission.

Method used

The cable employs silver-plated copper wire conductors, a multi-layered main insulation layer, and a hollow tube design. Combined with the interlocking and fixing of disulfide bond hot melt adhesive and rubber microspheres, along with multi-layered shielding and sheathing materials, it forms a low-loss, high-stability cable structure.

Benefits of technology

It achieves low-loss and high-stability signal transmission in high-frequency vibration scenarios, with stable characteristic impedance, reduced return loss, adaptability to high-speed signal transmission of 40Gbps and above, strong resistance to lateral pressure, and excellent vibration resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120767031B_ABST
    Figure CN120767031B_ABST
Patent Text Reader

Abstract

This invention discloses a low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios, its manufacturing method, and its application, belonging to the field of cable technology. The cable includes a silver-plated copper conductor and, from the inside out, a main insulation layer, a wire pair, a shielding layer, and a sheath. The main insulation layer consists of a sub-insulation layer and multiple parallel strip-shaped hollow tubes. The contact area between the sub-insulation layer and the hollow tubes is coated with a hot-melt adhesive containing disulfide bonds. The wire pair is formed by twisting two single wires; one wire has helical serrated protrusions, and the other has a matching groove. The contact area is filled with the aforementioned hot-melt adhesive, and the remaining gaps are filled with rubber microspheres. The shielding layer includes double-sided composite aluminum foil, a braided shielding layer, and drainage lines. The sheath is a graphene-containing polyolefin nanocomposite material. This invention achieves low-loss and high-stability transmission in high-frequency vibration scenarios through structural and material optimization, making it suitable for industrial automation, data centers, and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cable technology, specifically a low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios, its preparation method, and its application. Background Technology

[0002] With data transmission rates increasing to 40Gbps and above, higher demands are placed on the high-frequency transmission performance, anti-interference capabilities, and structural stability of communication cables. Traditional twisted-pair digital communication cables are gradually showing many shortcomings in meeting these requirements and are unable to meet the stringent standards of modern communication scenarios.

[0003] Specifically, the insulation layer of traditional cables often adopts a foamed structure, which not only has a high dielectric constant (usually ≥1.8) leading to large high-frequency dielectric attenuation, but also has weak resistance to lateral pressure, and places more stringent requirements on production equipment; after the wire pairs are twisted, they are easily loosened by external forces, causing fluctuations in the center-to-center distance of the conductors, which in turn leads to unstable working capacitance, directly affecting key performance such as characteristic impedance and return loss.

[0004] Furthermore, in high-frequency vibration scenarios such as industrial automation equipment (vibration frequency 10-500Hz, amplitude 0.1-0.5mm), the hollow insulation tubes of traditional cables are prone to air leakage, the wire pair "interlocking" is easily lost, and the shielding layer is easily worn. All of these factors lead to a degradation in high-frequency transmission performance, making it impossible to stably meet the requirements of 40Gbps high-speed transmission. Therefore, there is an urgent need for a twisted-pair digital communication cable that combines low loss, high stability, and vibration resistance. Summary of the Invention

[0005] The purpose of this invention is to provide a low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios, its preparation method, and its application, so as to solve the problems of easy delamination between layers, easy displacement of microspheres, unstable characteristic impedance, and large return loss of existing communication cables in high-frequency vibration environments, and to achieve stable and low-loss signal transmission of the cable under complex high-frequency vibration conditions, so as to meet the stringent performance requirements of communication cables in fields such as industrial automation and high-end equipment manufacturing.

[0006] The objective of this invention is achieved through the following technical solution:

[0007] A low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios includes a conductor, a main insulation layer, wire pairs, a shielding layer, and a sheath; the conductor is silver-plated copper wire.

[0008] The main insulation layer includes a sub-insulation layer and multiple hollow tubes. The sub-insulation layer is directly wrapped around the outer surface of the conductor, and the multiple hollow tubes are closely distributed in parallel strips along the outer edge of the sub-insulation layer to form a "multiple-wrapped 1" structure.

[0009] The insulating layer material is a blend of irradiated cross-linked polyethylene (XLPE), polycarbonate (PC), polyolefin-g-polycaprolactone (where g is grafted, PO-g-PCL), disulfide-functionalized polyolefin, and ethylene-octene copolymer (POE); the hollow tube material is a blend of irradiated cross-linked polyethylene (XLPE), polymethylpentene (PMP), and nano-kaolin, with its inner wall coated with a modified polyolefin microfilm and gas passing through it; the contact area between the hollow tube and the insulating layer is coated with irradiated cross-linked polyethylene-based hot melt adhesive containing disulfide bonds;

[0010] The wire pair is formed by twisting two structural single wires together. Each single wire consists of the conductor and a main insulation layer wrapped around its outside. The outer surface of one single wire has continuous spiral sawtooth protrusions (formed by multiple parallel hollow tubes working together), and the outer surface of the other single wire has corresponding spiral sawtooth grooves (formed by multiple parallel hollow tubes working together). The tooth shape and pitch of the protrusions and grooves are matched (the protrusions and grooves are fully fitted). The contact area between the grooves and protrusions is filled with the radiation cross-linked polyethylene hot melt adhesive containing disulfide bonds.

[0011] The shielding layer is wrapped around the outside of the wire pair and includes a double-sided composite aluminum foil, a braided shielding layer, and drainage lines. The double-sided composite aluminum foil is directly wrapped around the outer surface of the wire. The braided shielding layer is made of nickel-plated copper wire and braided on the outside of the double-sided composite aluminum foil. The drainage lines are arranged parallel to the inside of the braided shielding layer.

[0012] The sheath is wrapped around the outside of the shielding layer and is made of a graphene-containing polyolefin nanocomposite material.

[0013] In the above scheme, the structural function of the communication cable is as follows:

[0014] The conductor uses silver-plated copper wire. The silver plating reduces the skin effect during high-frequency signal transmission and lowers resistance loss. It is more suitable for stable transmission of high-speed signals of 40Gbps and above than ordinary copper wire, laying the foundation for overall low-loss performance.

[0015] The main insulation layer forms a composite insulation system with a tightly wrapped inner layer and an outer support layer. It can form an air medium through the gas inside the hollow tube, reducing the dielectric loss of high-frequency transmission. At the same time, the hollow tube adds extra support to the sub-insulation layer, making it more resistant to lateral pressure than traditional foamed insulation layers.

[0016] When the wire pair is fitted into the spiral sawtooth protrusion and groove, the disulfide-bonded irradiated cross-linked polyethylene hot melt adhesive filling the mating area plays a fixing role. The disulfide bonds in the hot melt adhesive can form dynamic covalent cross-links with the irradiated cross-linked polyethylene in the hollow tube material and the disulfide-bonded functionalized polyolefin in the insulation layer. Under high-frequency vibration, the stress is buffered by the breaking and recombination of bonds, avoiding wear or loosening caused by rigid collisions at the mating point. At the same time, it can fill the tiny gaps between the protrusion and groove mating surfaces, forming a sealing layer, reducing friction during vibration, and forming a synergy of rigid fixation and elastic buffering with the rubber microspheres in other areas of the twisting gap. This ensures that the protrusion and groove are fitted together, and absorbs vibration energy through the rubber microspheres, solving the contradiction of brittle fracture caused by excessive tightness or displacement caused by excessive looseness.

[0017] In the multi-layer shielding structure, double-sided composite aluminum foil is directly wrapped around the wire pairs, which can reflect low-frequency electromagnetic interference; the outer nickel-plated copper wire braided shielding layer can block high-frequency interference, and the nickel plating layer can also improve corrosion resistance; the drain wire is fixed by binding straps, which can quickly discharge the static electricity accumulated in the shielding layer and avoid electrostatic breakdown.

[0018] The sheath is made of a polyolefin nanocomposite material containing graphene, in which graphene is uniformly dispersed in the polyolefin substrate. This not only utilizes its high mechanical properties to improve the sheath's impact resistance and abrasion resistance, but also avoids the formation of a continuous conductive path (maintaining insulation).

[0019] The functions of materials in communication cables are as follows:

[0020] In the insulating layer materials, XLPE provides basic insulation and temperature resistance, ensuring dielectric stability at high frequencies; PC enhances material rigidity and strengthens resistance to lateral pressure. However, the polar PC in the insulating layer and the non-polar PMP in the hollow tube have poor compatibility, easily delaminating under long-term vibration and friction, disrupting the insulation continuity. PO-g-PCL acts as a molecular bridge, with its polar polycaprolactone branches (containing ester groups) forming intermolecular forces with the ester groups of PC, and the non-polar polyolefin backbone interacting with the carbon chains of XLPE and hollow PMP. This reduces the interfacial tension between PC and PMP, alleviates interlayer repulsion caused by polarity differences, and improves the compatibility of PC with XLPE and PMP. The disulfide-functionalized polyolefin in the insulating layer forms an initial covalent crosslink with the disulfide-containing XLPE-based hot melt adhesive coated on the hollow tube, providing basic bonding force for the interface between the insulating layer and the hollow tube. However, in high-frequency vibration scenarios of 10-500Hz, relying solely on covalent crosslinking can easily lead to fatigue fracture of the disulfide bonds. The addition of POE can absorb impact stress under high-frequency vibration due to its high elasticity, avoiding irreversible fracture of the disulfide bonds due to repeated stress impacts, and synergistically maintaining interlayer stability.

[0021] In the hollow tube, PMP has a low dielectric constant, which, together with the internal gas, further reduces the dielectric loss of the main insulation layer, making it suitable for high-frequency signal transmission; nano-kaolin is uniformly dispersed in the substrate, refining the material structure, improving the rigidity and wear resistance of the hollow tube, and mitigating the problem of tube wall damage during vibration; XLPE forms a compatible base with the XLPE substrate of the insulation layer, and together with disulfide bond hot melt adhesive, further strengthens the interlayer bonding.

[0022] In the line pair, the surface of the filled rubber microspheres is grafted with maleic anhydride and grafted with polyolefin. Its polar groups (-COOH) can form hydrogen bonds with the polar groups of the microspheres themselves (such as -F of fluororubber). At the same time, the non-polar segments are compatible with the polyolefin on the outer surface of the hollow tube, which enhances the interfacial adhesion between the microspheres and the hollow tube, reduces bouncing displacement during vibration, improves filling stability, and reduces the risk that the rubber microspheres may shift out of the gap under high-frequency vibration due to the weak interfacial adhesion between the rubber microspheres and the outer surface of the hollow tube.

[0023] In summary, this invention achieves low-loss and highly stable transmission in high-frequency vibration scenarios by optimizing the cable structure and materials.

[0024] As some possible embodiments of this application, in the insulating layer, the mass ratio of irradiated crosslinked polyethylene, polycarbonate, polyolefin-g-polycaprolactone, disulfide-functionalized polyolefin, and ethylene-octene copolymer is (3-4):1:(0.8-1.2):(0.02-0.03):(0.03-0.035).

[0025] In practical applications, if the proportion of irradiated cross-linked polyethylene is too low, the temperature resistance and flexibility of the insulation layer will decrease, making it prone to embrittlement. If the proportion of polycarbonate is too high, it will increase the polarity of the material and exacerbate the interfacial repulsion with the hollow tube. Insufficient PO-g-PCL will fail to effectively reduce interfacial tension, potentially leading to delamination. Insufficient disulfide-functionalized polyolefin will result in weak interlayer dynamic cross-linking, and delamination may still occur under vibration. The dosage provided by this invention ensures that irradiated cross-linked polyethylene dominates insulation and flexibility, polycarbonate moderately enhances rigidity, PO-g-PCL fully utilizes its compatibility, and disulfide bond materials effectively form dynamic cross-links, balancing insulation performance, mechanical strength, and interlayer stability.

[0026] As some possible implementations of this application, the thickness of the insulating layer is 0.1-0.2 mm; in the single wire with protrusions, the height of the spiral sawtooth protrusions is 0.03-0.05 mm, which matches the depth of the groove in the single wire with grooves.

[0027] As some possible implementations of this application, in the hollow tube, the mass ratio of irradiated cross-linked polyethylene, polymethylpentene, and nano-kaolin is (6-7):(2-3):(0.007-0.009).

[0028] In practical applications, if the proportion of polymethylpentene is too high, the material rigidity decreases, and the hollow tube is prone to deformation during coating. If the proportion is too low, the low dielectric advantage is insufficient, and the dielectric loss increases. Too much nano-kaolin will increase the material's brittleness, making it prone to cracking under vibration; too little will result in a weak reinforcing effect and insufficient wear resistance of the hollow tube. The parameters defined in this invention allow polymethylpentene to fully exert its low dielectric effect, irradiated cross-linked polyethylene to ensure structural stability, and nano-kaolin to moderately enhance wear resistance, thus enabling the hollow tube to balance low loss, rigidity, and durability.

[0029] As some possible embodiments of this application, the rubber microspheres are hydrogenated nitrile rubber / fluororubber blend microspheres with a mass ratio of 7:(3-5); the diameter of the rubber microspheres is 0.01-0.12 mm.

[0030] In practical applications, if only hydrogenated nitrile rubber is used, it is prone to compression set at high temperatures (such as 80°C), losing its filling function; if only fluororubber is used, the cost is high and the elasticity at room temperature is insufficient. If the microsphere diameter is too large, it cannot fill the small gaps; if it is too small, it is prone to aggregation, leading to dielectric inhomogeneity. Blended microspheres combine room temperature elasticity and high temperature stability, making them suitable for a wide range of vibration environments.

[0031] As one possible implementation of this application, in the shielding layer, a polyimide film pad with a thickness of 0.01-0.015 mm is provided between the double-sided composite aluminum foil and the woven shielding layer.

[0032] In practical applications, the aluminum foil and nickel-plated copper wire exhibit significant differences in thermal expansion. Temperature changes or vibrations can easily cause the aluminum foil to wrinkle or even tear, leading to a decrease in shielding effectiveness. Without a padding layer, this thermal stress acts directly on the aluminum foil, exacerbating the risk of damage. Polyimide film can buffer the difference in thermal expansion, reducing the stress on the aluminum foil; simultaneously, the film's flexibility absorbs vibrational impacts, preventing tearing caused by direct friction between the aluminum foil and the braided wire, thus maintaining the integrity of the shielding layer.

[0033] As some possible implementations of this application, in a single line with protrusions, the surface area of ​​the unprocessed protrusions of the hollow tube is provided with breathable micropores; in a single line with grooves, the surface area of ​​the unprocessed grooves of the hollow tube is provided with breathable micropores, the diameter of the breathable micropores is 500-800nm, they are distributed along the length of the single line, and the spacing between the pores is 20-50mm.

[0034] Polytetrafluoroethylene fibers grafted with maleic anhydride-acrylate copolymer are added to the hot melt adhesive filling the twisted gaps (i.e., the grooves and protrusions) of the online pair.

[0035] The double-sided composite aluminum foil has micro-perforations with a diameter of 0.01-0.02 mm every 8-20 cm along its length, with a perforation spacing of 3-15 mm and avoiding the drainage line fixing points; the binding straps are tied every 5-8 cm for 0.8-1.2 cm with a gap of 0.3-0.8 mm at intervals; the polyolefin nanocomposite material of the sheath contains polytetrafluoroethylene fibers grafted with maleic anhydride-acrylate copolymer.

[0036] In practical applications, the gas inside the hollow tube experiences pressure fluctuations due to temperature changes (such as sudden increases or decreases in ambient temperature) or vibrations, causing the tube to expand or contract, affecting the stability of the dielectric constant. Without micropores, the pressure cannot be released, potentially leading to tube rupture. Micropores allow minute amounts of gas to diffuse slowly, achieving dynamic pressure balance and reducing the impact of pressure fluctuations on the dielectric constant.

[0037] By adding polytetrafluoroethylene fibers to the hot melt adhesive at the interlocking points of the protrusions and grooves, a gas guiding channel can be formed to guide the diffusion of the exudated gas and prevent the gas from accumulating at the twisting points and forming local high pressure. The surface grafting layer can enhance the compatibility between the fibers and the hot melt adhesive substrate and prevent the fibers from shifting under high-frequency vibration.

[0038] The micro-perforations in the double-sided composite aluminum foil, the angle adjustment of the braided shielding layer, and the intermittent fixing of the binding straps provide an exhaust path for leaked gas, preventing it from accumulating in the shielding layer and causing the aluminum foil to wrinkle or tear.

[0039] The polytetrafluoroethylene fibers added to the sheath interweave to form a continuous breathable network during the sheath extrusion process. The gaps between the fibers form gas outlet channels, which can quickly discharge the gas accumulated inside the shielding layer to the outside, preventing the accumulation of air pressure inside the sheath from causing bulging.

[0040] The synergistic effect of the above design allows the hollow tube to maintain stable air pressure under temperature fluctuations and high-frequency vibrations, and controls the dielectric constant fluctuation of the main insulation layer to a lower range; the stability of the wire pair interlocking structure, shielding layer and sheath is enhanced, effectively resisting performance degradation under 10-500Hz vibration.

[0041] Furthermore, to achieve the above objectives, the present invention also provides a method for manufacturing a low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios, comprising the following steps:

[0042] S1. Wire drawing and conductor treatment: The copper wire is drawn and then silver-plated.

[0043] S2. Separate insulation layer extrusion: A blend of irradiated cross-linked polyethylene, polycarbonate, polyolefin-g-polycaprolactone, disulfide-functionalized polyolefin, and ethylene-octene copolymer is extruded onto the outer surface of the conductor using a gradient screw extruder to form a separate insulation layer;

[0044] S3. Hollow tube preparation and main insulation layer formation:

[0045] S31. Irradiated cross-linked polyethylene, polymethylpentene and nano-kaolin are blended and extruded into strip-shaped hollow tubes simultaneously through a multi-die co-extrusion process. Gas is introduced into the tube during extrusion, and the inner wall is coated with a modified polyolefin microfilm.

[0046] S32. The hollow tubes obtained in S31 are arranged in parallel and closely on the outer edge of the insulation layer of the two conductors, with the outer walls of the adjacent hollow tubes in contact. They are fixed on the bonding surface between the hollow tubes and the insulation layer by radiation-crosslinked polyethylene hot melt adhesive containing disulfide bonds, forming an overall hollow tube structure covering the insulation layer.

[0047] S33. The outer wall of the hollow tube structure outside one conductor is machined to form a continuous spiral sawtooth protrusion; the outer wall of the hollow tube structure outside the other conductor is machined to form a spiral sawtooth groove that matches the tooth shape and pitch of the protrusion; finally, two types of single wires with protrusions and grooves are formed.

[0048] S4. Pair Twisting and Filling: Twisting the raised single wire and the grooved single wire at a preset pitch to make the raised wire and the groove fit precisely;

[0049] The area where the protrusions and grooves meet is filled with irradiated cross-linked polyethylene hot melt adhesive containing disulfide bonds, and the area in the twisted gap where no protrusions and grooves are provided is filled with rubber microspheres grafted with maleic anhydride and grafted with polyolefin to ensure uniform filling.

[0050] S5. Shielding layer processing: online wrapping of double-sided composite aluminum foil, laying the drain line parallel on the outer surface of the double-sided composite aluminum foil (5), and then using polyolefin spiral binding tape to bind and fix the drain line together with the double-sided composite aluminum foil; finally, braiding nickel-plated copper wire to form a braided shielding layer, so that the drain line is wrapped inside the braided shielding layer.

[0051] S6. Sheath extrusion: Graphene-containing polyolefin nanocomposite material is extruded onto the outside of the shielding layer to form a sheath;

[0052] S7. Finished Product Inspection: Inspect the characteristic impedance, return loss, and dielectric constant fluctuation of the cable after vibration.

[0053] This invention, through a step-by-step process of conductor processing, main insulation layer preparation, and wire pair twisting, ensures that each structure is formed according to design parameters, improves product consistency and stability, and guarantees performance standards during mass production.

[0054] As some possible implementations of this application, in step S2, the barrel temperature of the gradient screw extruder is controlled in three sections: 140-160℃ in the feeding section, 180-210℃ in the melting section, and 210-230℃ in the die head section; and firstly, polyolefin-g-polycaprolactone and polycarbonate are premixed to form a masterbatch, which is then blended with irradiated crosslinked polyethylene, disulfide-functionalized polyolefin, and ethylene-octene copolymer.

[0055] In practical applications, when polyolefin-g-polycaprolactone (PO-g-PCL) is directly blended with polycarbonate, the significant difference in their amounts (PC as the main component and PO-g-PCL as an additive) can easily lead to uneven dispersion of PO-g-PCL, failing to fully utilize its "molecular bridging" function. Three-stage temperature control ensures complete melting and prevents degradation of the material. Premixed masterbatch utilizes the polar branches of PO-g-PCL to pre-combine with the ester groups of PC, ensuring uniform dispersion of compatible additives within the PC. When blended with XLPE and disulfide-functionalized polyolefins, this effectively mitigates the polarity difference between PC and XLPE, preventing delamination of the insulating layer. Furthermore, if PO-g-PCL is directly blended with XLPE, PC, and disulfide-bonded materials without premixing, insufficient dispersion due to the low amount of PO-g-PCL can exacerbate interfacial repulsion between PC and XLPE, leading to easy delamination under vibration.

[0056] As one possible implementation of this application, 0.5-1 wt% of ethylene-vinyl acetate copolymer is introduced into the insulating layer as a toughening agent.

[0057] The significant difference in hardness between PC and XLPE makes the interface prone to stress concentration at low temperatures. Combined with vibration and impact, this can lead to embrittlement and cracking of the insulating layer, affecting dielectric stability. The flexibility of EVA can reduce the hardness difference between PC and XLPE, improve the low-temperature toughness of the insulating layer, reduce the risk of embrittlement during low-temperature vibration, and maintain insulation integrity.

[0058] To achieve the above objectives, the present invention also provides the application of the aforementioned communication cable in high-frequency vibration equipment, such as industrial robotic arms (e.g., robotic arms in automotive welding production lines), high-frequency vibratory feeders (e.g., for electronic component sorting), and high-speed CNC milling machines (e.g., precision parts processing machine tools).

[0059] Compared with the prior art, the beneficial effects of the present invention are:

[0060] This invention achieves low-loss, high-stability transmission in high-frequency vibration scenarios by optimizing the cable structure and materials. The "multi-pack 1" main insulation layer consists of a sub-insulation layer and a gas-filled hollow tube, combined with low-dielectric materials to form a semi-air dielectric. This effectively solves the problem of high high-frequency loss in traditional insulation layers. Combined with silver-plated copper wire conductors to reduce high-frequency skin effect loss, it significantly improves high-frequency transmission performance (characteristic impedance stabilized at 100±1~100±2Ω, return loss reaching 26.3~28.7dB@1GHz), stably supporting high-speed signal transmission of 40Gbps and above, with high-frequency dielectric attenuation far lower than traditional cables.

[0061] The dynamic cross-linking of disulfide bonds and the compatibility design with polyolefin-g-polycaprolactone alleviate the polarity differences and thermal expansion stress of different materials, overcome the risk of delamination and thermal stress cracking, and enable the cable to remain stable under temperature fluctuations of -30℃ to 80℃ (after high and low temperature cycle testing, there were no abnormalities in the insulation layer and no displacement of rubber microspheres. After high temperature long-term testing, the sheath was intact, and the dielectric constant fluctuation was only 0.04 ~ 0.08), thus taking into account both temperature resistance and mechanical strength.

[0062] The wire pairs are interlocked and twisted through protrusions and grooves, and the rubber microspheres filling the gaps form a double fixation of "mechanical interlocking + elastic buffering", which ensures structural stability during vibration and effectively resists loosening caused by high-frequency vibration of 10-500Hz (after 100h of vibration at 10-500Hz and an amplitude of 0.3mm, the dielectric constant fluctuation is only 0.05~0.08, and the main insulation layer has no cracks or delamination). This solves the problems of wire pair interlocking failure and conductor center spacing fluctuation under vibration in traditional cables.

[0063] In summary, the solution of this invention is precisely adapted to the transmission requirements of high-frequency vibration scenarios such as industrial automation and data centers, and achieves low-loss and highly stable signal transmission. Attached Figure Description

[0064] Figure 1 Schematic diagram of the low-loss twisted-pair digital communication cable in Example 1;

[0065] Among them, 1-conductor, 2-insulation layer, 3-hollow tube, 4-wire pair, 5-composite aluminum foil, 6-drain wire, 7-braided shielding layer, and 8-sheath. Detailed Implementation

[0066] Example 1

[0067] A low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios, such as Figure 1 As shown, it includes conductor 1, main insulation layer, wire pair 4, shielding layer and sheath 8. The specific preparation method is as follows:

[0068] S1. Wire drawing and conductor 1 treatment: The copper wire is drawn to a diameter of 0.8 mm and then electroplated with silver. The silver layer thickness is 0.02 mm and the conductivity IACS is 105%.

[0069] S2. Extrusion of insulating layer 2:

[0070] Material preparation: Weigh out irradiated cross-linked polyethylene (XLPE), polycarbonate (PC), polyolefin-g-polycaprolactone (PO-g-PCL), disulfide-functionalized polyolefin, and ethylene-octene copolymer (POE, elongation at break ≥800%) in a mass ratio of 3.5:1:1:0.025:0.035. First, put PO-g-PCL and polycarbonate (PC) into a high-speed mixer and premix at 100°C for 15 min to prepare a masterbatch. Then, add XLPE, disulfide-functionalized polyolefin, and POE into a high-speed mixer and stir at 80°C for 10 min to form a blend.

[0071] Extrusion process: A gradient screw extruder is used, with the screw barrel temperature set to 160℃ in the feed section, 210℃ in the melt section, and 230℃ in the die head section. The blend is extruded onto the outer surface of conductor 1, and the extrusion speed is controlled at 1.5 m / min. It is quickly shaped by cooling water bath (water temperature 25℃), and finally forms a 0.2mm thick sub-insulation layer 2 (thickness deviation ≤ ±0.01mm).

[0072] S3. Preparation of hollow tube 3 and formation of main insulation layer:

[0073] S31. Material blending and tube preparation: Irradiated cross-linked polyethylene, polymethylpentene, and nano-kaolin were blended at a mass ratio of 6.5:2.5:0.008 and simultaneously extruded into 10 strip-shaped hollow tubes 3 (0.1 mm wall thickness) using a 10-die co-extrusion process. During extrusion, 0.3 MPa of air was introduced into the tubes, and the inner wall was coated with a 0.005 mm thick modified polyolefin microfilm (not shown in the figure).

[0074] S32. Parallel Arrangement: Ten hollow tubes 3 are arranged in parallel and closely around the outer edge of the insulating layer 2, with the outer walls of adjacent tubes in contact. They are then fixed to the bonding surface between the hollow tubes 3 and the insulating layer 2 using a radiation-crosslinked polyethylene hot melt adhesive (50% solid content) containing disulfide bonds, forming a single wire. Two single wires are prepared according to this method.

[0075] S33. Protrusion / Groove (both are common structures, not shown in the figure) processing: For one of the single lines, its outer wall is processed in an integrated manner according to a precise spiral trajectory, so that this group of hollow tubes 3 work together to form a continuous and complete spiral sawtooth protrusion (height 0.04mm); for the other single line, a matching spiral sawtooth groove is processed on its outer wall according to the same spiral trajectory, ultimately forming two types of single lines with protrusions and grooves.

[0076] S4. Wire pair 4 twist and fill:

[0077] Two types of single wires, one with protrusions and the other with grooves, are twisted together at a pitch of 15 mm to form wire pairs 4, thus preparing a total of 4 wire pairs 4 with the same structure (e.g., Figure 1 );

[0078] During the twisting process, a precision glue injection device is used to inject irradiated cross-linked polyethylene hot melt adhesive (50% solid content) containing disulfide bonds into the mating area of ​​the protrusion and the groove to fill the tiny gaps in the mating surface (adhesive layer thickness 0.002mm).

[0079] After the hot melt adhesive has initially cured (let it stand at room temperature for 5 minutes), rubber microspheres (hydrogenated nitrile rubber / fluororubber mass ratio 7:4, diameter 0.04 mm, surface grafted with maleic anhydride grafted polyolefin) are filled into the area of ​​the twisted gap where no protrusions or grooves are set, and the filling volume accounts for 35% of the gap area; 4 line pairs are arranged in parallel and in contact with each other.

[0080] S5. Shielding layer processing: On the online double-sided composite aluminum foil 5 with a total thickness of 0.025mm, copper drainage wires 6 with a diameter of 0.3mm are laid parallel to the outer surface of the double-sided composite aluminum foil 5; using polyolefin spiral binding tape with a width of 2mm, binding 1cm every 6cm with a 0.5mm gap, the drainage wires 6 are tied and fixed together with the double-sided composite aluminum foil 5; finally, 36 strands of nickel-plated copper wire are used to braid a braided shielding layer 7 (braiding density 92%), so that the drainage wires 6 are wrapped inside the braided shielding layer 7.

[0081] S6. Sheath 8 Extrusion:

[0082] Material preparation: Graphene was added to a polyolefin substrate (linear low-density polyethylene, melt flow rate 2.0 g / 10 min) at a mass ratio of 1:80. The substrate was then ultrasonically dispersed (500 W power, 30 min time, anhydrous ethanol as the dispersion medium, followed by vacuum drying to remove the medium) to prepare graphene masterbatch. This masterbatch was then fed into a twin-screw extruder and melt-sheared at 140-150℃ and a screw speed of 250 r / min to form a directly extrudable sheath composite material.

[0083] Extrusion process: The above composite material is extruded onto the outside of the shielding layer to form a sheath 8 with a thickness of 1.0 mm.

[0084] S7. Finished Product Inspection: Inspect characteristic impedance, return loss, and dielectric constant fluctuation after vibration.

[0085] Example 2

[0086] Compared to Example 1, the following differences exist:

[0087] S3. Preparation of hollow tube 3 and formation of main insulation layer: Weigh the materials at a mass ratio of 6:2:0.007 and extrude tube blanks (introduce air at 0.25MPa).

[0088] S4. Wire Pair 4 Twisting and Filling: Single wire twisting pitch 12mm, filled with rubber microspheres (hydrogenated nitrile rubber / fluororubber 7:3, diameter 0.04mm), filling volume 30%.

[0089] S5. Shielding layer processing: aluminum foil thickness 0.02mm, braided shielding layer 7 density 90%, drainage line 6 fixing method is the same as in Example 1.

[0090] The remaining steps or parameters are the same as in Example 1.

[0091] Example 3

[0092] Compared to Example 1, in step S2, 0.8 wt% of ethylene-vinyl acetate copolymer is introduced into the insulating layer 2 material, and it is blended with other materials before extrusion. The remaining steps are the same as in Example 1.

[0093] Example 4

[0094] Compared to Example 3, in step S5, a 0.012mm thick polyimide film pad (not shown in the figure) is added between the double-sided composite aluminum foil 5 and the braided shielding layer 7. The pad is arranged in a spiral wrapping manner with a wrapping overlap rate of 15%. The remaining steps are the same as in Example 3.

[0095] Example 5

[0096] Compared to Example 3, steps S3, S4, S5, and S6 are adjusted as follows, while the remaining steps are the same as in Example 3:

[0097] S3: After preparing two types of single-line materials, one with protrusions and the other with grooves, permeable micropores are provided on the surface areas of the hollow tube 3 where no protrusions or grooves have been processed. These permeable micropores (not shown in the figure) are processed using a precision laser drilling device. The permeable micropores have a diameter of 500 nm, are distributed along the length of the single-line (axial direction), and have a spacing of 25-35 mm (ensuring approximately 30-40 permeable micropores per meter of single-line material, while avoiding protrusion / groove areas). The micropores penetrate the modified polyolefin microfilm on the inner wall and the inner wall of the hollow tube 3, replacing the air inside the hollow tube 3 with xenon gas.

[0098] S4. Wire pair 4 twist and fill:

[0099] Two types of single wires prepared by S3 are twisted together with a pitch of 15 mm to form wire pairs 4, resulting in a total of 4 wire pairs 4 with the same structure (e.g., ...). Figure 1 );

[0100] During the twisting process, a precision glue injection device is used to inject a radiation-crosslinked polyethylene hot melt adhesive containing disulfide bonds [50% solid content, with 0.45wt% polytetrafluoroethylene short fibers added, the short fibers being 30-50μm in length and 1-2μm in diameter, with maleic anhydride-acrylate copolymer grafted on the surface (grafting rate 1.2-1.3%), aspect ratio 20-30:1] into the mating area, filling the tiny gaps in the mating surface (adhesive layer thickness 0.002mm).

[0101] After the hot melt adhesive has initially cured (let it stand at room temperature for 5 minutes), rubber microspheres (hydrogenated nitrile rubber / fluororubber mass ratio 7:4, diameter 0.04 mm, surface grafted with maleic anhydride grafted polyolefin) are filled into the area of ​​the twisted gap where no protrusions or grooves are set, and the filling volume accounts for 35% of the gap area; 4 line pairs are arranged in parallel and in contact with each other.

[0102] S5. Shielding layer processing: A double-sided composite aluminum foil 5 with a total thickness of 0.025mm is wrapped online. Micro-perforations of 0.015mm diameter are set every 15cm along the length of the aluminum foil (not shown in the figure), with a perforation spacing of 8mm. Copper drainage wires 6 with a diameter of 0.3mm are laid parallel to the outer surface of the double-sided composite aluminum foil 5, ensuring that the drainage wires 6 avoid the micro-perforations. Polyolefin spiral binding tape (not shown in the figure) is used to bind and fix the drainage wires 6 together with the double-sided composite aluminum foil 5, binding 1cm every 6cm with a 0.5mm gap at the interval. Finally, 36 strands of nickel-plated copper wire are braided at a 50° braiding angle to form a braided shielding layer 7 (braiding density 92%), so that the drainage wires 6 are wrapped inside the braided shielding layer 7.

[0103] S6. Sheath 8 Extrusion:

[0104] Graphene was added to a polyolefin substrate (linear low-density polyethylene, melt flow rate 2.0 g / 10 min) at a mass ratio of 1:80, and ultrasonically dispersed (power 500 W, time 30 min, dispersion medium is anhydrous ethanol, and the medium is removed by vacuum drying after ultrasonication) to prepare graphene masterbatch. Polytetrafluoroethylene short fibers (length 200-300 μm, diameter 10-15 μm, surface grafted with maleic anhydride-acrylate copolymer, grafting rate 1.2-1.5%) and graphene masterbatch were premixed at a mass ratio of 0.015:1 in a high-speed mixer (mixing temperature 70℃, speed 300 r / min, mixing time 15 min) to prepare PTFE-graphene composite masterbatch. The composite masterbatch was directly fed into a twin-screw extruder and melt-sheared at a temperature of 140-150℃ and a screw speed of 250 r / min to form a sheath composite material that can be directly extruded.

[0105] Extrusion process: The above composite material is extruded onto the outside of the shielding layer to form a sheath 8 with a thickness of 1.0 mm.

[0106] It is worth noting that in the above embodiments, the preparation methods of some materials are as follows:

[0107] ① Polyolefin-g-polycaprolactone: In a dry environment under argon protection, 500 mL of toluene was added to a 1000 mL polymerization reactor, followed by 12 mM of 1-hexene monomer. The mixture was stirred for 5 min to ensure uniform dispersion of the monomer, and the reaction temperature was adjusted to 60 °C. 0.1 mL of 0.5 mol / L triisobutylaluminum was added as a chain transfer agent, followed by 1 mM of (Ph3C)(B(C6F5)4) toluene solution. Finally, 0.5 mM of a toluene solution of 2-(N-(2,4,6-trimethylphenylimine)-o-isopropylphenyl-methyl)-6-(2-η-1-naphthyl)-pyridinedimethylzirconium catalyst was added. The polymerization reaction was carried out for 2 min under stirring to generate polyolefin segments. Then, 5 mM of 3-methyl-caprolactone monomer was added to the above reaction solution, and the temperature was raised to 85 °C for ring-opening polymerization for 12 h. After the reaction was completed, the solution was poured into ethanol to precipitate, filtered, washed, and dried under vacuum to finally obtain polyolefin-g-polycaprolactone.

[0108] ② Disulfide-functionalized polyolefins: In a dry 500 mL reaction flask, add 0.5 g of cis-2-butene-1,4-dithioacetate (CTA-1), 0.01 g of Grubbs third-generation catalyst (G3), and 20 g of cyclooctene (COE). Then add 100 mL of dichloromethane (DCM) and stir to dissolve, controlling the molar ratio of CTA-1 to G3 to be 100:1 and the COE concentration to be 2.0 M. After stirring the reaction at 25 °C for 4 h, pour the reaction solution into 5 times the volume of cold methanol to precipitate, filter to collect the solid, and dry under vacuum at 40 °C for 6 h to obtain disulfide-functionalized polyolefins.

[0109] ③ Rubber microspheres grafted with maleic anhydride and polyolefin: Take 70g of hydrogenated nitrile rubber and 30g of fluororubber (the dosage here is the dosage of Example 1; the dosage in Example 2 is adjusted according to the actual dosage), mix them on a two-roll mill at 120℃ for 10 min, crush them, and add 200mL of toluene to dissolve them into a rubber solution. Use spray drying (inlet air temperature 120℃, outlet air temperature 60℃) to make microspheres with a diameter of 0.04mm. Separately, take 5g of maleic anhydride grafted polyolefin and dissolve it in 100mL of toluene, add the above microspheres, stir at 60℃ for 2 h, filter, and vacuum dry at 50℃ for 4 h to obtain grafted microspheres.

[0110] The preparation method of maleic anhydride-grafted polyolefin is as follows: 100g of polyolefin (such as polyethylene), 5g of maleic anhydride, and 0.2g of dicumyl peroxide are added to a twin-screw extruder. The feed section temperature is 140℃, the melt section temperature is 160℃, the die head temperature is 170℃, and the screw speed is 200r / min. The mixture is melt-blended, extruded, and granulated to obtain maleic anhydride-grafted polyolefin.

[0111] ④ XLPE-based hot melt adhesive containing disulfides: Add 80 parts of irradiated cross-linked polyethylene (XLPE), 5 parts of diallyl disulfide, 15 parts of C5 petroleum resin, and 0.5 parts of antioxidant 1010 to a high-speed mixer and mix at 80°C for 10 minutes. Feed the mixture into a twin-screw extruder (feed section 140°C, melt section 160°C, die head section 170°C), melt-blend, and then extrude and granulate. Before use, heat and melt to a solid content of 50%.

[0112] ⑤ Modified polyolefin microfilm: 95g of low-density polyethylene (LDPE) and 5g of maleic anhydride modified polyethylene are added to a twin-screw extruder, melt-blended at 160℃, and then extruded through a T-die to form a film. The thickness is controlled to 0.005mm by biaxial stretching (longitudinal stretching ratio 3:1, transverse stretching ratio 3:1) to obtain the modified polyolefin microfilm.

[0113] ⑥ Polyolefin Spiral Strapping Tape: Add 60g of linear low-density polyethylene, 35g of magnesium hydroxide, 2g of silane coupling agent KH550, and 0.5g of antioxidant 168 to a high-speed mixer and mix at 100℃ for 15 min. After granulation of the mixture through a twin-screw extruder (feed section 150℃, melt section 170℃, die head section 180℃), extrude it through a spiral forming die (temperature 170℃), control the width to 2mm, and then wind it up after cooling to obtain the final product.

[0114] ⑦ Ethylene-vinyl acetate copolymer (EVA): 82g of ethylene monomer, 18g of vinyl acetate monomer, and 0.2g of dicumyl peroxide (initiator) were added to a high-pressure reactor. After nitrogen purging three times, the temperature was raised to 200℃, and the pressure was increased to 200MPa. The reaction was stirred for 4 hours. After depressurization and cooling, the product was granulated using a pelletizer to obtain EVA.

[0115] ⑧ Double-sided composite aluminum foil 5: Take two 0.0125mm thick aluminum foils, and evenly coat one of them with an acrylic adhesive (30% solid content), with a coating amount of 5g / m². 2 Dry in an 80℃ oven for 30 seconds. Lay another aluminum foil onto the coated surface, and then laminate it using a pressure roller with a pressure of 0.3MPa. After winding, you will get a double-sided composite aluminum foil with a total thickness of 0.025mm.

[0116] ⑨ Irradiated cross-linked polyethylene: In a dry environment protected by argon, 500 mL of toluene was added to a 1000 mL polymerization reactor, followed by 12 mM linear low-density polyethylene raw material. The mixture was stirred for 6 min, and the reaction temperature was adjusted to 60 °C. 0.1 mL of 0.5 mol / L triisobutylaluminum was added as a chain transfer agent, followed by 1 mM of (Ph3C)(B(C6F5)4) toluene solution. Finally, 0.5 mM of a toluene solution of 2-(N-(2,4,6-trimethylphenylimine)-o-isopropylphenyl-methyl)-6-(2-η-1-naphthyl)-pyridinedimethylzirconium catalyst was added, and the mixture was stirred for 2 min. The reaction product was then transferred to a twin-screw extruder for granulation. Finally, the product was irradiated using an electron accelerator with an electron beam energy of 2.0 MeV and an irradiation dose of 200 kGy. Argon gas was introduced during the irradiation process to form irradiated cross-linked polyethylene.

[0117] All other materials for which the preparation method is not specified are commercially available materials.

[0118] Comparative Example 1

[0119] Compared to Example 1, step S3 is omitted. Instead, a 0.3 mm thick insulating layer 2 (material same as in Example 1) is extruded outside the conductor 1 in step S2, and the process proceeds directly to step S4 for twisting. The remaining steps are the same as in Example 1.

[0120] Comparative Example 2

[0121] Compared to Example 1, in step S2, the insulating layer 2 material does not contain PO-g-PCL. The remaining steps are the same as in Example 1.

[0122] Comparative Example 3

[0123] Compared to Example 1,

[0124] In step S2, the insulating layer 2 material does not contain disulfide-functionalized polyolefin;

[0125] In step S3, when the hollow tube 3 is covered with the insulating layer 2, ordinary XLPE hot melt adhesive (without disulfide bonds) is applied.

[0126] The remaining steps are the same as in Example 1.

[0127] Comparative Example 4

[0128] Compared to Example 1, in step S2, PO-g-PCL and disulfide-functionalized polyolefin are not premixed into masterbatch, but are directly fed into an extruder for blending with XLPE, disulfide-functionalized polyolefin, and POE. The remaining steps are the same as in Example 1.

[0129] Comparative Example 5

[0130] Compared to Example 5, no polytetrafluoroethylene fibers were added to the hot melt adhesive. The remaining steps were the same as in Example 5.

[0131] Experimental Example

[0132] The twisted-pair digital communication cables prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to the following tests:

[0133] 1. Basic high-frequency performance.

[0134] Characteristic impedance: Frequency range 100MHz-1GHz, test environment temperature 23±2℃, relative humidity 50±5%, measured using a vector network analyzer, sampling interval 10MHz (according to IEC 61156-5 standard).

[0135] Return loss: Test frequency 1GHz, test environment same as characteristic impedance test, before test, the cable is kept at a constant temperature (23±2℃) for 24 hours, and the average measurement value of the total length of the cable (100m) is taken (according to IEC 61156-5 standard).

[0136] 2. Post-vibration performance.

[0137] Vibration conditions: 10-500Hz, amplitude 0.3mm, duration 100 hours (sinusoidal vibration test performed according to GB / T2423.10 standard, sweep rate 1oct / min, dwell time 5min at each frequency point);

[0138] Test indicators: Dielectric constant fluctuation after vibration (tested at 1MHz according to GB / T 1409 standard, with the initial dielectric constant before vibration as the reference, and the absolute value of the fluctuation is calculated), and the condition of the second insulating layer (the condition of the second insulating layer can directly reflect the overall stability of the main insulating layer, and its cracking or delamination will lead to the destruction of the insulation continuity of the main insulating layer) or the shielding layer. The condition inspection mainly checks whether there is delamination / cracking, etc., and observes with a metallographic microscope at 200x magnification.

[0139] 3. Temperature adaptability test.

[0140] ① High and low temperature cycling: -30℃ (hold for 2 hours) → 80℃ (hold for 2 hours), cycle 50 times.

[0141] Test indicators: State of insulation layer 2 after cycling (observed with a metallographic microscope at 200x magnification, the judgment criteria are the same as the state of insulation layer after vibration), displacement of microspheres in line pair 4 (observed with a metallographic microscope, displacement distance ≤0.01mm is judged as stable);

[0142] ②High temperature resistance: kept at 80℃ for 1000 hours.

[0143] Test indicators: Dielectric constant fluctuation after long-term endurance test (based on the initial dielectric constant before the high-temperature long-term endurance test, the test frequency is 1MHz, the fluctuation difference is taken as the absolute value, according to GB / T 1409 standard), and sheath cracking (observed by visual inspection combined with 50x microscope).

[0144] The test results are shown in Table 1.

[0145] Table 1:

[0146]

[0147] As shown in Table 1, the twisted-pair digital communication cables prepared in Examples 1-5 exhibited excellent comprehensive performance in various tests. Regarding basic high-frequency performance, the characteristic impedance was stably controlled within a certain range, and the return loss was good, ensuring low loss and high efficiency in high-frequency signal transmission. In the face of vibration, the dielectric constant fluctuation was small after vibration, and the insulation layer 2 and shielding layer structures remained stable without cracking, delamination, or other defects. In temperature adaptability tests, whether it was high-low temperature cycling or high-temperature endurance testing, the sheath 8 remained intact, the microspheres in the wire pair 4 did not shift, and the dielectric constant fluctuation remained at a low level, indicating that the cable can maintain stable performance under complex temperature conditions and meet practical application requirements.

[0148] The following is a detailed analysis of the embodiments and comparative examples:

[0149] Examples 1-2: Through structural and material optimization, characteristic impedance was controlled, resulting in low return loss. Excellent performance in vibration and temperature tests effectively buffered the effects of external stress and temperature changes.

[0150] Example 3: The introduction of EVA toughening agent significantly improved the temperature resistance of the sub-insulation layer 2. During high and low temperature cycling tests, sub-insulation layer 2 showed no embrittlement and maintained good performance in other indicators, demonstrating the effectiveness of EVA toughening agent in enhancing the toughness of sub-insulation layer 2 and improving the overall temperature adaptability of the cable.

[0151] Example 4: The addition of a polyimide film pad significantly improved the working condition of the shielding layer. During vibration testing, the shielding layer showed no tearing, and return loss was further reduced, indicating that the pad effectively reduced friction and stress concentration between the shielding layer and other components, thus improving the stability of the shielding layer and the signal transmission quality.

[0152] Example 5: The addition of breathable micropores has shown particularly outstanding performance in temperature adaptability testing. It effectively balances the air pressure fluctuations caused by temperature changes, resulting in minimal fluctuations in the dielectric constant of the cable during high-temperature long-term and high-low temperature cycle tests. The sheath 8 and internal structure remain stable, demonstrating the good adaptability of this design to extreme temperature environments.

[0153] Comparative Example 1: Without the hollow tube 3, the insulation layer 2 lacks sufficient support under vibration and temperature changes, resulting in a decrease in resistance to lateral pressure, easy cracking, and a significant degradation in high-frequency performance.

[0154] Comparative Example 2: The lack of PO-g-PCL compatibilizer resulted in poor interfacial compatibility between PC and PMP materials. Under vibration, the insulation layer 2 was prone to delamination, affecting the performance of the cable.

[0155] Comparative Example 3: In a dynamic cross-linking system constructed without disulfide bonds, the interlayer bonding relies solely on physical bonding. Under vibration and temperature stress, the interlayer adhesion is insufficient, leading to local delamination of insulation layer 2 and a decrease in performance. This demonstrates the importance of dynamic cross-linking technology in enhancing interlayer bonding and improving the structural stability of cables.

[0156] Comparative Example 4: The lack of premixing masterbatch treatment for PO-g-PCL and disulfide bond materials resulted in uneven dispersion of the materials in the cable system, causing significant fluctuations in the performance of insulation layer 2.

[0157] Comparative Example 5: After reducing the polytetrafluoroethylene fibers in the hot melt adhesive, the gas could not be discharged, and the accumulated gas destroyed the disulfide bond crosslinking between the hot melt adhesive and the hollow tube 3.

[0158] In summary, the technical solutions proposed in this invention, including structural optimization, material innovation, and process control, have significant effects on improving the performance of twisted-pair digital communication cables under high-frequency vibration and complex temperature environments, providing reliable technical support for the application of twisted-pair digital communication cables in practical complex environments.

Claims

1. A low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios, comprising a conductor (1), a main insulation layer, wire pairs (4), a shielding layer, and a sheath (8); characterized in that: The conductor (1) is a silver-plated copper wire; The main insulation layer includes a sub-insulation layer (2) and multiple hollow tubes (3). The sub-insulation layer (2) directly covers the outer surface of the conductor (1), and the multiple hollow tubes (3) are closely distributed on the outer edge of the sub-insulation layer (2) in a parallel strip distribution to form a "multiple-covered 1" structure. The insulating layer (2) is made of a blend of irradiated cross-linked polyethylene, polycarbonate, polyolefin-g-polycaprolactone, disulfide-functionalized polyolefin, and ethylene-octene copolymer; the hollow tube (3) is made of a blend of irradiated cross-linked polyethylene, polymethylpentene, and nano-kaolin, with a modified polyolefin microfilm coated on its inner wall and gas passing through it; the contact area between the hollow tube (3) and the insulating layer (2) is coated with a disulfide-containing irradiated cross-linked polyethylene-based hot melt adhesive. The wire pair (4) is formed by twisting together a single wire with protrusions and a single wire with grooves. Each single wire is composed of the conductor (1) and a main insulation layer wrapped around its outside. The outer surface of the single wire with protrusions is provided with continuous spiral sawtooth protrusions, and the outer surface of the single wire with grooves is provided with corresponding spiral sawtooth grooves. The tooth shape and pitch of the protrusions and grooves are matched. The mating area between the grooves and protrusions is filled with the radiation cross-linked polyethylene hot melt adhesive containing disulfide bonds. The twisted gap of line pair (4) is not provided with protrusions and grooves. The area is filled with rubber microspheres grafted with maleic anhydride and grafted with polyolefin. The shielding layer is wrapped around the outside of the wire pair (4) and includes a double-sided composite aluminum foil (5), a braided shielding layer (7) and a drain line (6). The double-sided composite aluminum foil (5) is directly wrapped around the outer surface of the wire pair (4). The braided shielding layer (7) is made of nickel-plated copper wire and braided on the outside of the double-sided composite aluminum foil (5). The drain line (6) is arranged parallel to the inside of the braided shielding layer (7). The sheath (8) is wrapped around the outside of the shielding layer and is made of a graphene-containing polyolefin nanocomposite material.

2. The low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios according to claim 1, characterized in that: In the insulating layer (2), the mass ratio of irradiated crosslinked polyethylene, polycarbonate, polyolefin-g-polycaprolactone, disulfide-functionalized polyolefin, and ethylene-octene copolymer is (3-4):1:(0.8-1.2):(0.02-0.03):(0.03-0.035).

3. The low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios according to claim 1, characterized in that: The thickness of the insulating layer (2) is 0.1-0.2 mm; in the single wire with protrusions, the height of the spiral sawtooth protrusions is 0.03-0.05 mm, which matches the depth of the groove in the single wire with grooves.

4. The low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios according to claim 1, characterized in that: In the hollow tube (3), the mass ratio of irradiated cross-linked polyethylene, polymethylpentene and nano-kaolin is (6-7):(2-3):(0.007-0.009).

5. The low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios according to claim 1, characterized in that: The rubber microspheres are hydrogenated nitrile rubber / fluororubber blend microspheres with a mass ratio of 7:(3-5); the diameter of the rubber microspheres is 0.01-0.12 mm.

6. The low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios according to claim 1, characterized in that: In the shielding layer, a polyimide film pad with a thickness of 0.01-0.015 mm is provided between the double-sided composite aluminum foil (5) and the braided shielding layer (7).

7. The low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios according to claim 1, characterized in that: In the single line with protrusions, the surface area of ​​the unprocessed protrusions of the hollow tube (3) is provided with breathable micropores; in the single line with grooves, the surface area of ​​the unprocessed grooves of the hollow tube (3) is provided with breathable micropores; the diameter of the breathable micropores is 500-800nm, distributed along the length of the single line, and the spacing between the pores is 20-50mm. Polytetrafluoroethylene fibers grafted with maleic anhydride-acrylate copolymer are added to the hot melt adhesive filling the twist gap of (4) online; The double-sided composite aluminum foil (5) has micro-perforations with a diameter of 0.01-0.02 mm every 8-20 cm along its length, with a hole spacing of 3-15 mm and avoiding the fixing point of the drainage line (6); the binding strap is tied every 5-8 cm for 0.8-1.2 cm and a gap of 0.3-0.8 mm is left at the interval; The sheath (8) is made of polyolefin nanocomposite material with polytetrafluoroethylene fibers grafted with maleic anhydride-acrylate copolymer.

8. The method for manufacturing a low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Wire drawing and conductor treatment: The copper wire is drawn and then silver-plated. S2. Extrusion of the insulating layer (2): Using a gradient screw extruder, a blend of irradiated cross-linked polyethylene, polycarbonate, polyolefin-g-polycaprolactone, disulfide functionalized polyolefin and ethylene-octene copolymer is extruded onto the outer surface of the conductor (1) to form the insulating layer (2). S3. Preparation of hollow tube (3) and formation of main insulation layer: S31. Irradiated cross-linked polyethylene, polymethylpentene and nano-kaolin are blended and extruded into strip-shaped hollow tubes (3) simultaneously through multi-die co-extrusion process. Gas is introduced into the tube during extrusion and the inner wall is coated with modified polyolefin microfilm. S32. The hollow tubes (3) obtained in S31 are arranged in parallel and closely on the outer edge of the insulation layer (2) of the two conductors, with the outer walls of the adjacent hollow tubes (3) in contact. The hollow tubes (3) are fixed on the bonding surface of the hollow tubes (3) and the insulation layer (2) by irradiated cross-linked polyethylene hot melt adhesive containing disulfide bonds, forming an overall hollow tube structure covering the insulation layer. S33. The outer wall of the hollow tube (3) outside one conductor is processed to form a continuous spiral sawtooth protrusion; the outer wall of the hollow tube (3) outside the other conductor is processed to form a spiral sawtooth groove that matches the tooth shape and pitch of the protrusion; finally, two types of single wires with protrusions and grooves are formed. S4. Pair Twisting and Filling: Twisting the raised single wire and the grooved single wire at a preset pitch to make the raised and groove fit precisely; The area where the protrusions and grooves meet is filled with irradiated cross-linked polyethylene hot melt adhesive containing disulfide bonds, and the area in the twisted gap where no protrusions and grooves are provided is filled with rubber microspheres grafted with maleic anhydride and grafted with polyolefin to ensure uniform filling. S5. Shielding layer processing: wrap double-sided composite aluminum foil (5) around (4) online, then lay the drain line (6) parallel on the outer surface of the double-sided composite aluminum foil (5), and then use polyolefin spiral binding tape to bind and fix the drain line (6) together with the double-sided composite aluminum foil (5); finally, braid nickel-plated copper wire to form a braided shielding layer (7). S6. Sheath extrusion: Graphene-containing polyolefin nanocomposite material is extruded onto the outside of the shielding layer to form a sheath (8). S7. Finished Product Inspection: Inspect the characteristic impedance, return loss, and dielectric constant fluctuation of the cable after vibration.

9. The method for manufacturing a low-loss twisted-pair digital communication cable suitable for high-frequency vibration scenarios according to claim 8, characterized in that, In step S2, the barrel temperature of the gradient screw extruder is controlled in three sections: 140-160℃ in the feeding section, 180-210℃ in the melting section, and 210-230℃ in the die head section. Polyolefin-g-polycaprolactone is first premixed with polycarbonate to form a masterbatch, and then blended with irradiated crosslinked polyethylene, disulfide functionalized polyolefin, and ethylene-octene copolymer.

10. The application of a communication cable as described in any one of claims 1-7 in a high-frequency vibration device.

Citation Information

Patent Citations

  • High-frequency coaxial cable

    CN102738549A

  • Shielded control cable

    CN217405176U